Relationships between social support, work-family conflict and coping with psychosocial well-being among single mothers in Malacca, Malaysia - Rahman, Noor Watee (2021)
This study aimed to identify the relationships between psychosocial well-being and social support, work-family conflict, and coping among working single mothers in Melaka, Malaysia. This study used a quantitative approach and survey technique with descriptive analyses. Besides, the moderator analysis was performed to measure the moderating effect of coping on the relationship between independent and dependent variables. A total of 364 single mothers working in government agencies in the state of Melaka participated in this study. An online survey with a self-administered questionnaire was employed to collect data. The questionnaire collected data on demographic background, social support [based on The Multidimensional Scale of Perceived Social Support (MSPSS)], work-family conflict [Work-family Conflict (WFC) Scale], coping [Ways of Coping Checklist (WoCC) Scale], and psychosocial well-being (Psychosocial Well-being Scale). Findings revealed that respondents showed a moderate level of social support and work-family conflict, while above 50% of respondents showed high level of coping and psychosocial well-being. The ANOVA revealed that there was a significant difference in psychosocial well-being based on age and education level. Furthermore, the findings indicated that social support (family, friend, and significant other) and coping had a positively relationship with psychosocial well-being while work-family conflict (work interference with family and family interference with work) had a negatively relationship with psychosocial wellbeing. The multiple regression analysis showed that predictor variables, namely age, education, social support, and work-family conflict had significantly predicted psychosocial well-being. Meanwhile, the results of aggression analysis using the stepwise method showed that friend support and significant other support were the most important predictors in predicting psychosocial well-being followed by work interference with family. The regression analysis also revealed that friend support was the most significant predictor in predicting psychosocial well-being followed by work interference with family. Next, the moderator test indicated that coping was a moderator of the relationships between psychosocial well-being and social support and work-family conflict. The findings imply that a support from family, friends, and significant other would increase the ability to cope and reduce psychological distress. For example, in drafting any related programmes, the element on coping must be taken into consideration when planning programmes for single mothers to enhance their psychosocial well-being.